Nonlinear Control Techniques for Enhanced Stability in Renewable Energy Systems - Muhammad Abdullah Khan; Usman Tariq Chaudhry (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2024)
Renewable energy systems, particularly those incorporating solar and wind power, are prone to stability issues due to the intermittent and fluctuating nature of these energy sources. This paper investigates several nonlinear control techniques—namely, adaptive control, sliding mode control, and fuzzy logic control—that are designed to improve stability in renewable energy systems. Through simulations, we demonstrate how these methods can effectively reduce fluctuations and maintain stable energy output, offering a robust approach to enhancing the reliability of renewable energy systems.